2010
DOI: 10.1007/s11159-010-9176-6
|View full text |Cite
|
Sign up to set email alerts
|

Job stress and locus of control in teachers: comparisons between samples from the United States and Zimbabwe

Abstract: This study examines the relationship between educators' locus of control and job stress using samples from the US and Zimbabwe. Multiple regression analyses are used to identify significant relationships in the US sample between teachers' external locus of control and the severity of the job stress that they experience, coupled with the perceived degree of organisational support received. However, this relationship between the locus of control and stress indices could not

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This result provides support for the significant effect of personal character on sports behavior. Crothers et al [38] argued that people who lack internal control tend to encounter emotional exhaustion and discomfort. On the other hand, people with internal control are less stressful.…”
Section: Discussionmentioning
confidence: 99%
“…This result provides support for the significant effect of personal character on sports behavior. Crothers et al [38] argued that people who lack internal control tend to encounter emotional exhaustion and discomfort. On the other hand, people with internal control are less stressful.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to Bennett et al [ 16 ], people with a strong IHLC and PHLC use smartphone applications to take an active role in their health, while those with CHLC tendencies do not. In particular, Croster et al [ 17 ] found that people lacking an IHLC tend to experience emotional depletion and discomfort, while those with high levels can expect their IHLC to protect them from COVID-19-induced stressors.…”
Section: Introductionmentioning
confidence: 99%
“…Teachers and student teachers with an internal locus of control report lower stress than those with external ones (Huston, 1989;Lunenberg & Cadavid, 1992;Sadowski & Blackwell, 1985, 1987. This is particularly true for teachers in the United States (Crothers et al, 2011). If teachers believe that teacher evaluations are not a reliable and valid measure of their teaching (see Berliner, 2014, andCollins &Amrein-Beardsley, 2014), they may attribute their evaluations to luck rather than their own capabilities.…”
Section: Teacher Stress Job Satisfaction Morale and Locus Of Controlmentioning
confidence: 99%